Inflammatory status predicts contact lens discomfort under adverse environmental conditions - Fernández, Itziar (2020)
Purpose: To characterize and predict the clinical and tear molecular response of contact lens (CL) wearers ex-posed to a controlled adverse desiccating environment (CADE).Methods: Objective and subjective variables and tear cytokine levels were evaluated of monthly silicone hydrogel CL wearers pre- and post-90 min of CADE exposure. Unsupervised hierarchical agglomerative clustering based on relative change from baseline values was used to identify response profiles (clusters). A multiple logistic regression model was used to identify cluster membership predictors.Results: Forty-seven CL wearers were divided into 3 clusters having similar age (mean: 27.7 7.7 years) and sex distribution. All of them showed a significant (p < 0.05) increase in limbal hyperemia and staining after CADE exposure. Additionally, Cluster-1 (n = 22, 46.8%) membership was characterized by a significant (p 0.05) higher worsening of corneal and limbal staining, increased CL wear symptoms, and reduced epidermal-growth-factor and increased interleukin (IL)-4 and IL-6 tear levels. Cluster-2 (n = 22, 46.8%) showed no changes (p 0.05) in symptoms after CADE; however, their IL-12p70, monocyte-chemoattractant-protein-1 and regulated-on-activation, normal-T-cell-expressed-and-secreted (RANTES) post-exposure tear levels significantly (p < 0.05) increased. Finally, Cluster-3 (n = 3, 6.4%) mainly showed significant higher blink rate (78.1 +/- 21.7) during CADE. Corneal staining and tear IL-12p70 levels were identified as Cluster-1 membership predictors.Conclusions: Most of silicone hydrogel CL wearers exposed to CADE showed a worsening of the ocular surface integrity and an upregulated tear inflammatory status. However, only half of them reported worsening of CL wear symptoms. These CL wearers were detected based on corneal integrity and tear inflammatory status. These findings can help reduce CL wear discontinuation and drop out.